Paradoxes in leaky microbial trade - Yoav Kallus (Nature Portfolio, 2017)
Microbes live in communities and exchange metabolites, but the resulting dynamics are poorly understood. Here, the authors study the interplay between metabolite production strategies and population dynamics, and find that complex and unexpected dynamics emerge even in simple microbial economies.